2017
DOI: 10.1111/jam.13348
|View full text |Cite
|
Sign up to set email alerts
|

The effect of burdock leaf fraction on adhesion, biofilm formation, quorum sensing and virulence factors ofPseudomonas aeruginosa

Abstract: This study introduces a natural and effective bacterial biofilm inhibitor, which could also significantly decrease the content of virulence factors and the drug resistance of P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
(87 reference statements)
1
5
0
Order By: Relevance
“…Present results showed that garlic extracts, nisin, ε-polylysine, and citric acid decreased the growth, EPS production, bacterial surface hydrophobicity, and biofilm formtion of B. subtilis. This is in agreement with previous studies which found that bacterial biofilm and the adhesion rate on surfaces can be reduced by reducing the production of EPS with antibacterial substance (Branda et al, 2006;Lou, Wang, & Tang, 2017;Rathi & Satheesh, 2012).…”
Section: Re Sults and Discussionsupporting
confidence: 93%
“…Present results showed that garlic extracts, nisin, ε-polylysine, and citric acid decreased the growth, EPS production, bacterial surface hydrophobicity, and biofilm formtion of B. subtilis. This is in agreement with previous studies which found that bacterial biofilm and the adhesion rate on surfaces can be reduced by reducing the production of EPS with antibacterial substance (Branda et al, 2006;Lou, Wang, & Tang, 2017;Rathi & Satheesh, 2012).…”
Section: Re Sults and Discussionsupporting
confidence: 93%
“…Quorum Sensing regulates various bacterial behaviors, such as the formation of biofilm and the secretion of virulence factors (such as elastase, rhamnolipid, and pyocyanin; Lou et al, 2017). QS inhibitors are able to interfere with the QS system of pathogens and reduce the pathogenic effects, However, the majority of QS inhibitors have been found to be toxic, and cannot be used in medicine fields.…”
Section: Anti-qs Activitymentioning
confidence: 99%
“…The method with reference to Lou et al was slightly modified [ 22 ]. Briefly, 100 μL of supernatant was obtained by centrifuging the bacterial solution (the same as item 2.8), extracted twice by adding ethyl acetate, evaporated at 40 °C, dissolved by adding 100 μL of ultrapure water, reacted by adding 300 μL of a 2% anthrone-sulfuric acid solution in boiling water for 15 min, and cooled.…”
Section: Methodsmentioning
confidence: 99%